RACISM ISSUES IN NIKE BRAND ADVERTISEMENT - Rafi, Muhammad Abyan; Jasjfi, Elda Franzia (VCD, 2021)
Racialism is a social issue that has become a culture in major countries. Many protest movements against social issues, starting from the community, an organization, to a well-known brand, one of which is Nike. Nike is one of the most well-known and successful sports brands in terms of products and athletes in all sports. This is one of the keys to the success of the Nike brand in awakening the world to the issue of racism, which is widely shown through its visual campaign in the form of an official Nike poster advertisement entitled “Believe in something. Even if it means sacrificing everything "Colin Kaepernick," Speaking up doesn't always make life easier. But easy never changed anything "Raheem Sterling, and George Floyd's official video ad" For once, Don't do it ". The three controversial official Nike advertisements are an interesting topic to discuss in this journal. The method used is a descriptive qualitative method that aims to find out what visual forms the Nike brand is trying to raise in raising the issue of racism by describing the context surrounding the event, describing how the process happened to become an official advertising campaign in the form of a visual object using the technique. semiotics in describing it. The results of this study are to find out how the visual form of Nike's official brand advertisements in conveying the current issue of racism and with a semiotic approach we can find out how Nike is in delivering campaigns about the issue of racism in order to form understanding and sensitivity to the social issues of racism around us. Keywords: racism, advertisement, poster, video, brand, Nike